Siła organizacji międzynarodowych i jej wyznaczniki - Michał Drgas (Ksiegarnia Akademicka Publishing, 2018)
The Power of International Organizations and Its Determinants The article examines the power of international organizations and factors that determine its  resence and amount. It shows how international organizations are capable of using both the „classically” understood power, one that is aimed towards specific actors and causes its  ffects directly, and different forms of „structural” power that either affect the behavior of objects that remain unspecified or influence their constitution as social beings of a particular kind.  The factors that were identified as determining the power include knowledge, labor, financial resources and other material resources, acting as efficient causes, will, being the enabling cause, and authority, related to both types of causality.